Technical Education and Vocational Training for Sustainable Development (Journal of Training and Development, 2015)
Technical Education and Vocational Training is taken as an integral part of the national development. This has an important role in the national sustainable development. The knowledge, skills and attitudes are the overall aspects of the lifelong learning. In the context of Nepal, it has provided skills and jobs to many people who are away from the general education having several barriers within them. TEVT covers all the FIETS aspects of sustainability. This study has tried to highlight the major essence of the Technical Education and Vocational Training for the Sustainable Development of the nation. This paper has made an attempt to promote the TEVT through the perspectives of sustainable development. So it has highlighted on the aspects of education for sustainable development and the barriers behind it.DOI: http://dx.doi.org/10.3126/jtd.v1i0.13085 Journal of Training and Development Vol.1 2015: 15-20